Hydro-chemical Survey and Quantifying Spatial Variations in Groundwater Quality in Coastal Region of Chennai, Tamilnadu, India – a case study - Kishan Singh Rawat; T. German Amali Jacintha; Sudhir Kumar Singh (Faculty of Geography, Universitas Gadjah Mada, 2018)
The good quality of groundwater is important for the purpose of future planning and management. The present study has been undertaken to provide an overview on the status of groundwater quality through physicochemical parameters namely pH, alkalinity, total hardness, total dissolved solids, chloride, fluoride, nitrate, phosphate and iron through laboratory analysis. Samples have been collected from seven wells located in Chennai costal region of state Tamilnadu, India. The laboratory-based results shows that the mean value of pH is 7.29, alkalinity (308.57 mg/l), total hardness (285.71 mg/l), chloride (175.71 mg/l), iron (0.71 mg/l), nitrate (13.57 mg/l), phosphorus (2.71 mg/l) and total dissolved solids (924 mg/l), respectively. The geo-database water quality parameters were created in Geographical an Information System. Further, the kriging a geo-statistical method of interpolation is applied to know the health of groundwater in the then-sampled area. This interpolation method has been used to predict spatial distribution physicochemical parameters in the form of contour. Local planners and policy makers may utilize these results for efficient management of groundwater resources in this area.